Effect of Folic Acid and Vitamin B12 Supplementation on Homocysteine Level in association with MTHFR C677T Polymorphisms in Overweight Female Adults - Fidelia Fiddelia (Biomedical Engineering, 2015)
UNCORRECTED PROOFFOR REVIEWERBEBIOMEDICAL ENGINEERINGjournal homepage: be.ub.ac.idEffect of Folic Acid and Vitamin B12 Supplementation on Homocysteine Levelin association with MTHFR C677T Polymorphisms in Overweight FemaleAdultsFidelia Fidelia1, Antonius Suwanto1, Felicia Kartawidjajaputra2†, Susana Susana21 Faculty of Biotechnology, Atma Jaya Catholic University, Jakarta2Bioanalytical Laboratory Nutrifood Research Center, PT Nutrifood Indonesia, JakartaA R T I C L E I N F OArticle history:Received: February 2015Accepted: June 2015Available online:August 2015Keywords:Cardiovascular diseaseFolateHomocysteineMethylenetetrahydrofolatereductase C677TVitamin B12†Corresponding author:Bioanalytical LaboratoryNutrifood Research Center,PT Nutrifood Indonesia,JakartaE-mail:felicia@nutrifood.co.idA B S T R A C T1. IntroductionCardiovascular disease (CVD) is known as theleading cause of death and disability worldwide,including Indonesia. In 2008, an estimated of 17.3million people died from CVDs and by 2030, it ispredicted to be risen over 23 million people.Atherosclerotic heart disease, or widely known ascoronary heart disease (CHD) is one of CVDgroup occupied the first place of cause of death inIndonesia and the number keeps rising over theyears [1-3].There are many factors associated withincreased risk of CVD. Some of risk factors areclassified as non-modifiable, such as age, sex andgenetics; whereas behavioral risk factors, such asphysical inactivity, tobacco use, unhealthy diet,and harmful use of alcohol, which are responsiblefor about 80% of atherosclerotic heart disease, areable to be modified by lifestyle or pharmaceuticalintervention. Both of modifiable and nonmodifiablefactors can lead to intermediate riskfactors, such as hypertension, hyperlipidemia,glucose intolerance and overweight or obesity,which can lead to chronic disease development[4].80-90% of people dying from CHD have one ormore major risk factors that are influenced bylifestyle. Among the numerous factors above,overweight is one to be highlighted especiallybecause the incidence is increasing each year.World Health Organization stated that theprevalence of overweight in Indonesian women isObjective: The aim of this study was to evaluate the effect of folic acid and vitamin B12 supplementation on Hcylevel based on the MTHFR C677T polymorphisms in Indonesian overweight females.Methods: The study involved 110 female adults (20±1.3 years) with a body mass index (BMI) above 22.9 (mean:25.3±2.3). DNA was extracted from saliva in order to identify the SNP of MTHFRC677T using PCR-RFLP. 15 of 110subjects were chosen to represent all MTHFR genotypes (5 CC, 6 CT and 4 TT) and assigned two differenttreatments: control (placebo), and supplement (500μg folic acid and 1 mg vitamin B12) for 4 weeks. Hcy levelswere measured using direct immunochemical assay.Result: This study population (n=110) showed that 677CC allele had the highest frequency (67%), followed by677CT (29%) and 677TT (4%). The results demonstrated no significant differences of Hcy level among allsubjects before treatment, but Hcy level was slightly higher in T allele subjects. The folate and vitamin B12treatment significantly reduced the level of Hcy in supplement group (p = 0.038), but not in placebo group. Thedifference between placebo and treatment was observed to be the highest in TT, followed by CT and CC subjects.Conclusion: This study showed that subjects who had T allele, tended to have a higher level of Hcy.Supplementation of folate and vitamin B12 was proven to lower the level of Hcy, and TT subjects were proven tobe the most responsive.